English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

7 answers

x² + 6x + 9

(x + 3)(x + 3) = x² + 3x + 3x + 9 = x² + 6x + 9

- - - - - -s-

2006-12-09 01:23:46 · answer #1 · answered by SAMUEL D 7 · 0 0

x^2 + 6x + 9 = 0
Help: Find factors of 9 that the sum equals 6.
Possible Factors: 1,3,9
Usable: 3
so..
(x+3)(x+3)=0
I'm sure you heard of FOIL...First, Inner, Outer, Last...means
x*x + x*3 + 3*x + 3*3 = 0
since (x+3)(x+3)=0,
ANS: then x=-3, x=-3
NOTE: Be sure to have both -3's as the answer.

2006-12-09 01:49:59 · answer #2 · answered by Jared H 2 · 0 0

x^2+6x+9=(x+3)^2

2006-12-09 01:33:40 · answer #3 · answered by yupchagee 7 · 0 0

x^2+6x+9=(x+3)^2

2006-12-09 01:21:34 · answer #4 · answered by telzey 2 · 1 0

(x^2+6x+9) = 0
(x+3)(x+3)=0
(x+3)^2=0
x=-3

2006-12-09 03:23:31 · answer #5 · answered by Kim T 1 · 0 0

x2+6x+9=0
(x+3)(x+3)=0
so x= -3

p.s that is so if only it is equal to zero

2006-12-09 01:23:48 · answer #6 · answered by pigley 4 · 0 1

(x+3) (x+3): factor of your given equation
xsub1=-3 xsub2=-3 :the zeros or the roots of your given equation

2006-12-09 01:34:50 · answer #7 · answered by Anonymous · 0 0

fedest.com, questions and answers